Evaluation of heat tolerance of Iraqi local goats - Oras Razoqi Waheb; Salih Hassan Al-Azzawi; Raeed Ibrahim Khalil (Zien Journals, 2022)
Temperature and humidity have a significant impact on the welfare and productivity of livestock. This study was conducted in the ruminant farm of the College of Agriculture at the University of Diyala. This study aimed to show the effect of each of the hair color of the local Iraqi goats, horns, dangles and pregnancy on each of the body temperature, rectal temperature, respiratory rate, thermal endurance coefficient and thermal adaptation coefficient for the month of August. The body, rectal temperature and thermal adaptation coefficient during the month of August in the afternoon. As for the thermal endurance coefficient, the opposite was observed, as it was higher in the morning reading than the evening reading
Keywords: heat stress; physiologica; Iraqi goat